2020
DOI: 10.5194/amt-13-205-2020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of TROPOMI/Sentinel-5 Precursor NO<sub>2</sub> observations with ground-based measurements in Helsinki

Abstract: Abstract. We present a comparison between satellite-based TROPOMI (TROPOspheric Monitoring Instrument) NO2 products and ground-based observations in Helsinki (Finland). TROPOMI NO2 total (summed) columns are compared with the measurements performed by the Pandora spectrometer between April and September 2018. The mean relative and absolute bias between the TROPOMI and Pandora NO2 total columns is about 10 % and 0.12×1015 molec. cm−2 respectively. The dispersion of these differences (estimated as their standard… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
152
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 207 publications
(169 citation statements)
references
References 30 publications
13
152
0
4
Order By: Relevance
“…Prevalence rate (per 100,000) NO 2 levels (μmol/m 2 ) levels as a proxy for overall air pollution. This metric was closely associated with ground levels of this contaminant in a validation study in the study area as well as in other European urban areas (Ialongo et al, 2020;Lorente et al, 2019). In vitro studies have shown that NO 2 can alter expression and synthesis of pro-inflammatory mediators in human bronchial cells (Bayram et al, 2001;Blomberg et al, 1997;Blomberg et al, 1999;Devalia et al, 1993;Mirowsky et al, 2016), thus increasing inflammation and hyperresponsiveness of epithelial cells.…”
Section: Total Casesmentioning
confidence: 56%
“…Prevalence rate (per 100,000) NO 2 levels (μmol/m 2 ) levels as a proxy for overall air pollution. This metric was closely associated with ground levels of this contaminant in a validation study in the study area as well as in other European urban areas (Ialongo et al, 2020;Lorente et al, 2019). In vitro studies have shown that NO 2 can alter expression and synthesis of pro-inflammatory mediators in human bronchial cells (Bayram et al, 2001;Blomberg et al, 1997;Blomberg et al, 1999;Devalia et al, 1993;Mirowsky et al, 2016), thus increasing inflammation and hyperresponsiveness of epithelial cells.…”
Section: Total Casesmentioning
confidence: 56%
“…To validate the satellite measurements, coincident groundbased data are required. The coincidence criteria are normally composed of spatial, temporal and quality control criteria (e.g., Boersma et al, 2018;Drosoglou et al, 2017;Griffin et al, 2019;Irie et al, 2008;Toohey and Strong, 2007). For example, in Zhao et al (2019b), the coincidence criteria used to pair ground-based observations (Pandora) and OMI data include (1) the nearest (in time) measurement that was within ±30 min of the OMI overpass time, (2) the closest OMI ground pixel (having a distance of less than 20 km from the ground pixel centre to the location of the Pandora instrument), and (3) cloud fraction < = 0.3 (the effective geometric cloud fraction as determined by the OMCLDO2 algorithm), and only high-quality OMI data are used (VcdQual-ityFlags = 0) (Celarier et al, 2016).…”
Section: Standard Approachmentioning
confidence: 99%
“…Total vertical column NO 2 can be measured by groundbased UV-visible remote sensing instruments using directsun, zenith-sky, or off-axis spectroscopy techniques (Cede et al, 2006;Drosoglou et al, 2017;Herman et al, 2009;Lee et al, 1994;Noxon, 1975;Piters et al, 2012;Roscoe et al, 2010;Vaughan et al, 1997). These measurements are of high quality and good precision and have been widely used for atmospheric chemistry studies (e.g., Adams et al, 2012;Hendrick et al, 2014) and satellite validations (e.g., Celarier et al, 2008;Drosoglou et al, 2018;Irie et al, 2008;Wenig et al, 2008). Among all these different viewing geometries, direct-sun measurements are of high accuracy and are not dependent on radiative transfer models (RTMs) to calculate air mass factors (AMFs) (Herman et al, 2009) or on knowledge of other atmospheric constituents.…”
Section: Introductionmentioning
confidence: 99%
“…Tropospheric NO 2 is mostly produced at high temperatures in combustion processes but also in soil microbial process and lightning events. In the stratosphere, NO 2 is an ozone-depleting substance produced primarily from the oxidation of nitrous oxide (N 2 O) (Crutzen, 1970;Johnston, 1971;Seinfeld and Pandis, 2006). NO x can also suppress ozone depletion by converting reactive chlorine and hydrogen compounds into unreactive reservoir species (Murphy et al, 1993).…”
Section: Introductionmentioning
confidence: 99%